A new species of the Genus Praon Haliday, 1833 (Hymenoptera, Braconidae: Aphidiinae). - Subba Rao, B. R.; Prakash, Sarup; Sharma, A. K. (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There is described a new species of Braconidae: Praon nympheae from India. Nomenclatural Acts nympheae Subba Rao, Sarup & Sharma, 1963 (Praon), spec. n.